Wildlife & natural resource management - Deal, Kevin, H. (Albany, N.Y. Delmar Pubs., 1998)
A textbook which surveys the field of wildlife management and describes the various types of animals, birds, reptiles, amphibians, and fish that must be preserved.
Keywords: Wildlife management